Promotion and Marketing Communication Strategiees to Increas the Presence of Mahar Agung Wedding Organizer in Surabaya - Ryan Arsy Hidayatullah; Lia Nirawati (Jurnal Ekonomi dan Bisnis Digital, 2026)
The development of digital technology and social media has driven changes in promotional strategies in the service industry, including wedding organizers. This study aims to analyze the promotional and marketing communication strategies implemented by Mahar Agung Wedding Organizer Surabaya in improving and maintaining the company's existence amid fierce competition. This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Data analysis was conducted using IFAS, EFAS, and SWOT matrices to identify internal and external factors of the company. The results show that Mahar Agung Wedding Organizer has dominant internal strengths and considerable external opportunities, placing it in Quadrant I of the SWOT matrix with a growth-oriented strategy. However, based on the IFAS and EFAS rankings, the company is also in a hold and maintain strategy position. Therefore, optimizing digital promotion, differentiating Javanese culture, improving operational efficiency, and strengthening customer loyalty are the main strategies for maintaining business sustainability.